COLLABORATIVE EFFORTS IN SCIENCE AND TECHNOLOGY WITHIN HIGHER EDUCATION INSTITUTIONS INSIGHTS AND REFLECTIONS - Hoang, Quyen Minh (Graduate Program of Universitas Tarumanagara, 2024)
In today's era of extensive international integration, collaboration in the realm of education and science and technology is undeniably essential within higher education establishments. Specifically, both bilateral and multilateral cooperative efforts in science and technology are being increasingly highlighted and encouraged in various forms. This article delves into the landscape of scientific and technological collaboration within higher education institutions, exploring the frameworks, experiences, and lessons learned from various perspectives. The development of science and technology stands as a cornerstone in the global integration agenda, with nations around the world emphasizing the importance of diversified and multilateral cooperation. Vietnam, in its pursuit of scientific excellence and technological prowess, has embraced international integration schemes and policies aimed at enhancing cooperation and investment in the realm of science and technology. This commitment is reflected in governmental decisions, policies, and strategic plans that underscore the significance of collaboration in research, development, and knowledge dissemination. Furthermore, international experiences, particularly from countries like Germany, the Czech Republic, Sweden, and China, offer valuable insights into different models of collaboration between higher education institutions, businesses, and research entities. These models encompass a spectrum of activities ranging from institutional exchanges, student programs, and scientific workshops to in-depth research partnerships and technology transfer initiatives. The article also delves into regional collaboration experiences, highlighting exemplary institutions such as Hanoi National University and the University of Labor and Social Affairs, showcasing their achievements, policies, and strategic initiatives in fostering collaborative endeavors in science and technology. Through case studies and analysis, we aim to extract lessons, best practices, and recommendations that can further enhance collaborative frameworks, communication channels, and resource utilization in the pursuit of scientific advancements and technological innovations. By examining the intersection of academia, industry, and international partnerships, this article aims to contribute to the ongoing discourse on effective strategies for promoting collaboration, knowledge exchange, and technology transfer within higher education ecosystems.